Effect of a recent parenteral dexamethasone and ketoprofen administration on the immunological diagnosis of tuberculosis in goats - Ortega, Javier; de Juan, Lucia; Sevilla, Iker A.; Garrido, Joseba M.; Roy, Álvaro; Velasco, Carlos; Romero, Beatriz; Domínguez, Mercedes; Pérez de Val, Bernat; Nebot, Carolina; Sáez-Llorente, José Luis; Álvarez, Julio; et al. (Frontiers in Veterinary Science, 2022)
Caprine tuberculosis (TB) is a zoonosis caused by members of the Mycobacterium tuberculosis complex (MTBC). Caprine TB eradication programmes are based mainly on intradermal tuberculin tests and slaughterhouse surveillance. Different factors may affect the performance of the TB diagnostic tests used in caprine herds and, therefore, their ability to detect infected animals. The present study evaluates the effect of the fraudulent administration of two anti-inflammatory substances, dexamethasone and ketoprofen, on the performance of the TB diagnostic techniques used in goats, as well as the suitability of high performance liquid chromatography (HPLC) for their detection in hair samples. The animals (n=90) were distributed in three groups: (1) a group treated with dexamethasone (n=30); a second group treated with ketoprofen (n=30); and a third non-treated control group (n=30). Both dexamethasone and ketoprofen groups were subjected to intramuscular inoculation with the substances 48 h after the administration of bovine and avian purified protein derivatives (PPDs), that is, 24 h before the tests were interpreted. All the animals were subjected to the single and comparative intradermal tuberculin (SIT and CIT, respectively) tests, interferon-gamma release assay (IGRA) and P22 ELISA. The number of SIT test reactors was significantly lower in the dexamethasone (p=0.001) and ketoprofen (p<0.001) groups 72 h after the bovine PPD inoculation compared with the control group. A significantly higher number of positive reactors to IGRA was detected within the dexamethasone group (p=0.016) 72 h after PPD administration compared to the control group. Dexamethasone and ketoprofen detection in either hair or serum samples was challenging when using HPLC since these substances were not detected in animals whose skin fold thickness (SFT) was reduced, what could be an issue if they are used for fraudulent purposes. In conclusion, the parenteral administration of dexamethasone or ketoprofen 48 h after the PPDs administration can significantly reduce the increase in SFT (mm) and subsequently the number of positive reactors to SIT test.